Cardiovascular system modeling and simulation - Aye Aye Khaing (2008)
This report deals with modeling and computer simulation of the cardiovascular system. The modeling focuses on the left heart and the complete cardiovascular system modeled close to the actual heart. Specific attention is given to the modeling of blood flow in the cardiovascular system. The cardiovascular system has been modeled using compartmental modeling for the arteries and veins. In this study, the analogy between parameters and variables that characterizes the left heart and corresponds to electrical circuit quantities is explored for the modeling as well as simulation. The simple model of the left heart is first simulated using half-square waveform as the inputs to run the model. The complete heart is also modeled using the lumped capacitance circuit and is followed by an improvement using a single-loop circuit. Finally, a complete model of a nonlinear pulsatile-flow patient model is developed. The use of the pulsatile model yields the desired accuracy, and the execution time is reduced. To complete the simulator, a mass pharmacologic model of SNP (pharmacokinetic and pharmacodynamic models) is also determined, and combined with the cardiovascular model. The common method for most pharmacologic agents to treat hypertension is relaxing the considered arterioles to decrease the resistance of peripheral blood flow.